PENGARUH KEPEMIMPINAN KEPALA SEKOLAH, KOMUNIKASI ORGANISASI TERHADAP KINERJA GURU DIMEDIASI KEPUASAN KERJA ( Studi Kasus Guru SMK Negeri di Lingkungan Sekolah Menengah Kejuruan Kota Demak ) - Sulistiyowati, Hesti; Liana, Lie (Jurnal Ilmiah Telaah Manajemen, 2015)
This study aims to examine and analyze the influence of the leadership and organizational communicationis mediated the job satisfaction of teachers job performance at SMK N Demak .This research type is a field research using a quantitative approach. The population are 120 teachers at SMK N Semarang. The techniques of data analyze use multiple linier analyze model test; R60 2. test, F test, and the hypothesis test use t test, and mediation effects ( path analyze ) . The results of the test as follows : leadership has positive and significant impact on the organi-zational communication; organi-zational communication has positive and significant impact on the job satisfaction; the leadership doesnt have positive and significant impact on the job performance; the organizational communication has positive and significant effect on the job performance, the job satisfaction has positive and significant effect on the job performance; leadership has positive and significant effect on teachers performance through the mediation of the job satisfaction; the organizational communication has positive and significant influence more effectively direct impact on teachers performance through the mediation of the job satisfaction .Keywords : leadership, organizational communication, job satisfaction, teachers jobperformance.